Ubiquitous Nature of Fluoroquinolones: The Oscillation between Antibacterial and Anticancer Activities - Temilolu Idowu; Frank Schweizer (MDPI AG, 2017)
Fluoroquinolones are synthetic antibacterial agents that stabilize the ternary complex of prokaryotic topoisomerase II enzymes (gyrase and Topo IV), leading to extensive DNA fragmentation and bacteria death. Despite the similar structural folds within the critical regions of prokaryotic and eukaryotic topoisomerases, clinically relevant fluoroquinolones display a remarkable selectivity for prokaryotic topoisomerase II, with excellent safety records in humans. Typical agents that target human topoisomerases (such as etoposide, doxorubicin and mitoxantrone) are associated with significant toxicities and secondary malignancies, whereas clinically relevant fluoroquinolones are not known to exhibit such propensities. Although many fluoroquinolones have been shown to display topoisomerase-independent antiproliferative effects against various human cancer cells, those that are significantly active against eukaryotic topoisomerase show the same DNA damaging properties as other topoisomerase poisons. Empirical models also show that fluoroquinolones mediate some unique immunomodulatory activities of suppressing pro-inflammatory cytokines and super-inducing interleukin-2. This article reviews the extended roles of fluoroquinolones and their prospects as lead for the unmet needs of "small and safe" multimodal-targeting drug scaffolds.